Factors Contributing to Sex Differences in Health‐Related Quality of Life After Ischemic Stroke: BASIC (Brain Attack Surveillance in Corpus Christi) Project - Phan, Hoang T.; Reeves, Mathew J.; Gall, Seana; Morgenstern, Lewis B.; Xu, Yuliang; Lisabeth, Lynda D. (Journal of the American Heart Association, 2022)
Background Women have been reported to have worse health-related quality of life (HRQoL) following stroke than men, but uncertainty exists over the reasons for the sex difference. Methods and Results We included all ischemic strokes registered with the BASIC (Brain Attack Surveillance in Corpus Christi) project (May 2010-December 2016), a population-based stroke study, who completed a 90-day outcome interview. Information on baseline characteristics was obtained from medical records and in-person interviews. HRQoL was measured by the 12-item short-form Stroke Specific Quality of Life Scale. Multivariable Tobit regression was used to estimate the mean difference in overall HRQoL scores (range, 1-5; higher indicating better HRQoL) between sexes and to identify contributing factors to the differences. We included 1061 cases with complete data on HRQoL and covariates (median age, 67 years; 51% women). In unadjusted analyses, women had poorer overall HRQoL than men (mean difference, -0.26 [95% CI, -0.40 to -0.13]). Contributors to this difference included sociodemographic/prestroke factors (eg, age, race and ethnicity, prestroke function), risk factors/comorbidities (eg, history of stroke, Alzheimer disease/dementia), and initial stroke severity. Sociodemographic/prestroke factors explained 62% of the sex difference (mean difference, -0.08 [95% CI, -0.21 to 0.04]). In a fully adjusted model that included adjustment for all confounding factors, the sex difference was eliminated and became nonsignificant (mean difference, -0.03 [95% CI, -0.16 to 0.09]). Conclusions Poorer HRQoL in women compared with men was observed and explained by the combination of sociodemographic and prestroke factors, including physical function before stroke and stroke severity. The findings suggest potential subgroups of women who might benefit from more targeted interventions before and after stroke to improve HRQoL.